2017
DOI: 10.1177/1538574417740508
|View full text |Cite
|
Sign up to set email alerts
|

Nonenhanced MRI Planning for Endovascular Repair of Abdominal Aortic Aneurysms: Comparison With Contrast-Enhanced CT Angiography

Abstract: Computed tomography angiography remains the standard of reference for EVAR planning; NC-MRI can be an option for patients with contraindications for CTA, in particular those with renal impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…However, due to the non-extensive availability of this method, its high cost, and the long duration, it is not frequently included in the post-EVAR follow-up. An MRI should be considered in patients with a continuous growth of the aneurysmal sac and negative or unclear findings at CTA [ 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to the non-extensive availability of this method, its high cost, and the long duration, it is not frequently included in the post-EVAR follow-up. An MRI should be considered in patients with a continuous growth of the aneurysmal sac and negative or unclear findings at CTA [ 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Mirza et al showed high sensitivity values (94%), with 88% specificity [ 31 ]. The high values for endoleak detection with CEUS were due to its high sensitivity to identify low-flow endoleaks as compared with CTA [ 30 ]. Moreover, CEUS, thanks to its ability to visualize in real time the direction and type of blood flow, provides endoleak characterization [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Modern imaging techniques can provide a detailed and highly accurate information about arterial supply of the kidneys. In this context, particularly useful seems to be computed tomography (CT) which is characterized by one of the highest spatial resolution of all radiological methods [8, 9].…”
Section: Introductionmentioning
confidence: 99%